2018
DOI: 10.1007/s00253-018-8877-9
|View full text |Cite
|
Sign up to set email alerts
|

Enriching ruminal polysaccharide-degrading consortia via co-inoculation with methanogenic sludge and microbial mechanisms of acidification across lignocellulose loading gradients

Abstract: Using lignocellulosic materials as substrates, ruminal microbiota were co-inoculated with anaerobic sludge at different loading rates (LR) to study the microbial community in the semi-continuous mode. The results indicated that the highest CH yield reached 0.22 L/g volatile solid at LR of 4 g/L/day, which obtained 56-58% of the theoretical value. In the steady stage with LR of 2-4 g/L/day and slurry recirculation, copies of total archaea increased. Especially the Methanobacteriales increased significantly (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Interestingly, at 0–15 cm soil depth, the bacterial phylum Cloacimonetes and the class Spirochaetia were the taxa uniquely found in unfertilized conventional tillage (CTN0), whereas the newly recognized phylum Berkelbacteria (Wrighton et al, 2014) was uniquely found in conventional fertilized tillage (CTN200). Cloacimonetes is a mesophylic phylum able to degrade cellulose and produce methane, while the members of Spirochaetia degrade cellulose and chitin (Limam et al, 2014; Chojnacka et al, 2015; Dai et al, 2016; Deng et al, 2018) and anaerobically decompose organic matter (Baba et al, 2014). Moreover, the phylum Berkelbacteria is an ATP binding and a putative transcriptional regulator with helix-turn-helix (HTH)-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, at 0–15 cm soil depth, the bacterial phylum Cloacimonetes and the class Spirochaetia were the taxa uniquely found in unfertilized conventional tillage (CTN0), whereas the newly recognized phylum Berkelbacteria (Wrighton et al, 2014) was uniquely found in conventional fertilized tillage (CTN200). Cloacimonetes is a mesophylic phylum able to degrade cellulose and produce methane, while the members of Spirochaetia degrade cellulose and chitin (Limam et al, 2014; Chojnacka et al, 2015; Dai et al, 2016; Deng et al, 2018) and anaerobically decompose organic matter (Baba et al, 2014). Moreover, the phylum Berkelbacteria is an ATP binding and a putative transcriptional regulator with helix-turn-helix (HTH)-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they were widely present in CK and TG. Many studies have reported that Ruminofilibacter can effectively degrade lignin substrates [43][44][45]. Bacillus was confirmed as a good species that can utilize carbohydrates with high efficiency [44].…”
Section: Bacterial Community Characteristicsmentioning
confidence: 99%
“…The microbiome shared by all DNA types (fDNA, iDNA, totDNA; Figure S1a) represented typical orders for farm-scale reactors and included a classical community performing AD (Calusinska et al, 2018;Deng et al, 2018).…”
Section: Bacterial Communitiesmentioning
confidence: 99%